PENGARUH TIME BUDGET PRESSURE DAN TASK COMPLEXITY TERHADAP KUALITAS PROSES AUDIT DENGAN TEKNIK AUDIT BERBANTUAN KOMPUTER (TABK) SEBAGAI VARIABEL MODERASI - Intan Desti Putrianti, (2023)
This study aims to determine the effect of time budget pressure and task complexity on the quality of the audit process with CAAT as a moderating variable. This research is a quantitative research with primary data types using a questionnaire and a Likert scale as a measuring tool. The population in this study were all auditors who worked at KAP DKI Jakarta. Determination of the sample in this study using a purposive sampling technique. A total of 183 questionnaires were distributed and 132 questionnaires were returned and only 115 questionnaires could be processed. The data analysis method used is Structural Equation Modeling (SEM) analysis. The results showed that time budget pressure and task complexity have a significant negative effect on the quality of the audit process. While the moderating variable cannot weaken the effect of time budget pressure and task complexity on the quality of the audit process. Future researchers are expected to be able to add independent variables and conduct pilot tests on the questionnaire indicators they wish to use.